Efficacy of modified rice straw fibre on properties of cementitious composites. (10th December 2020) - Shang, Xiaoyu; Yang, Jingwei; Song, Qun; Wang, Lei
Abstract: Appropriate treatment/disposal of rice straw as an agricultural waste has been a big challenge in rural areas. In this study, rice straw was recycled as a cheap and renewable fibre for enhancing the performance of cement-based composites. To improve the properties of fibre, two modification approaches were designed, namely, room-temperature (20 °C) alkaline (sodium hydroxide) treatment, and high-temperature (90 °C) alkaline treatment. The physicochemical characteristics of raw and modified straw fibres were analysed by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and fibre uniaxial stretching. The results showed that alkali-solution treatment increased cellulose proportion, slenderness ratio, tensile strength of fibre, and reduced its water absorption. Between two modification schemes, high-temperature treatment was more effective than the room-temperature treatment. The fibre modification eliminated the inhibitory effect of straw fibre on cement hydration verified by isothermal calorimeter analysis. Mechanical strength results illustrated that the addition of raw straw fibre had a marginal or even adverse effect on the mechanical properties of composites, due to its inherent porous structure and suppression effect on cement hydration. By contrast, the incorporation of modified fibres enhanced flexural strength and compressive strength of composites by 12.5%–22.3% and 4.7%–14.6%, respectively, especially for the addition of high-temperature treated fibre. Therefore, rice straw fibre after high-temperature alkaline treatment can be recycled for reinforcing cementitious composites, particularly suitable for on-site construction use in rural areas. Graphical abstract: Image 1 Highlights: Alkaline modification enhanced physicochemical properties of rice straw fibre. High-temperature alkaline treatment was effective for removing unfavourable components. Alkaline modification eliminated the inhibitory effect of straw fibre on cement hydration. Raw straw fibre had an adverse effect on the mechanical properties of composites. Modified fibre performed a superior efficiency for reinforcing the strength of composites.